MANAGEMENT OF REFRACTORY LARGE MACULAR HOLE WITH AUTOLOGOUS NEUROSENSORY RETINAL FREE FLAP TRANSPLANTATION. Issue 11 (November 2020) - Chang, Yo-Chen; Liu, Pei-Kang; Kao, Tzu-En; Chen, Kuo-Jen; Chen, Yi-Hsien; Chiu, Wei-Jun; Wu, Kwou-Yeung; Wu, Wen-Chuan
Abstract : Purpose: To investigate the morphological and functional outcome of refractory large macular hole (MH) with autologous neurosensory retinal free flap transplantation. Methods: This case series enrolled 10 patients suffering from refractory large MH at Kaohsiung Medical University Hospital, Kaohsiung, Taiwan. All eyes underwent pars plana vitrectomy, a neurosensory retinal free flap with a 1.5 to 2-MH diameter was harvested. We used an adhesive agent such as whole blood or Viscoat to assist the stabilization of the retinal free flap and then use tamponade silicone oil to tamponade the vitreous cavity. Silicone oil was removed 6 months postoperatively. Main outcome measures including closure of MH and change in best-corrected visual acuity change were recorded. Results: The mean age was 64.9 ± 11.5 years. Before presentation, all cases had received at least two vitreoretinal procedures including vitrectomy, internal limiting membrane peeling, and fluid–gas exchange. At last visit, closure of the MH was achieved in 9 of 10 (90%) cases. The mean preoperative best-corrected visual acuity and that after 12 months of surgery improved from 1.65 ± 0.43 logarithm of minimum angle of resolution to 0.88 ± 0.49 logarithm of minimum angle of resolution ( P < 0.001). Conclusion: For eyes with refractory or large MH, autologous neurosensory retinal free flap under silicone oil tamponade may provide a new option to improve the anatomical and function outcome, especially in cases where insufficient internal limiting membrane is left. Abstract : Autologous neurosensory retinal free flap transplantation assisted with whole blood or Viscoat showed a better closure rate of hole and significant improvement of visual function for refractory large macular hole.